Haemorrhoidal LASER Procedure (HeLP)- A painless Treatment for Haemorrhoid - Rahman, ASM ZAhidur; Rahman, Tanjilur; Hasan, Mehedi; Chandra, Sushanta (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: According to the vascular theory arterial overflow in the superior haemorrhoidal arteries would lead to dilatation of the haemorrhoidal venous plexus. The technique helps to promote the obliteration of the terminals of the superior rectal artery. The objective of this study is to describe the results of 100 patients with hemorrhoidal disease treated by the Hemorrhoidal LASER Procedure technique. Method: Under SAB anesthesia terminal arteriole of the upper rectal arteries were fulgurated by fiber laser diode, causing interruption of hemorrhoidal flow. This procedure is repeated circumferentially, following the clockwise positions.This procedure can be performed as a day care surgery. Results: Between January 2018 to January 2019, 100 patients underwent the Hemorrhoidal LASER Procedure technique for hemorrhoidal disease grades I, II and III. Total 100 patients were treated with HeLP procedure. Among them number of men was 81 and female was 19.The procedure proved to be successful at 3 month follow up of 92% patient. No major adverse effects or complications were reported. Post operative minor pain that required medication was 5 cases (5% patient). Postoperative minor bleeding was observed in 3 cases that were managed conservatively. At 3 month after procedure resolution of symptoms were observed in 88% cases with overall satisfaction rate was 89%. Significantly higher quality of life was observed in laser haemorrhoidal procedure. Conclusion: Hemorrhoidal LASER Procedure is a painless outpatient technique .It is a safe, effective, improve symptoms & chance of cure is high compared to other conventional surgery. Similar benefits are seen for patient with severe anal spasm, external thrombosis, fissure and sentinel tags & fistula. J Bangladesh Coll Phys Surg 2020; 38(1): 18-22